The correlation between red blood cell distribution width to serum albumin ratio and all-cause mortality in critically ill patients with chronic obstructive pulmonary disease: a retrospective study using the MIMIC-IV database - Zhang, Qianqian; Liu, Ling; Zhou, Jing; Teng, Gang; Wang, Yuanyuan; Zhang, Nianzhi (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) significantly contributes to critical illness and mortality in intensive care units (ICU), yet validated prognostic biomarkers are limited. The red blood cell distribution width to albumin ratio (RAR), which reflects systemic inflammation and nutritional imbalance, has shown predictive value in chronic kidney disease and diabetes. However, its association with mortality in critically ill COPD patients has not been explored. This study investigates the relationship between RAR and all-cause mortality in this high-risk population.MethodsUtilizing the MIMIC-IV database, 3,779 patients admitted to the ICU for the first time and diagnosed with COPD between 2008 and 2019 were included. Patients were categorized into four groups (Q1-Q4) based on the RAR quartiles within 24 h of admission. Kaplan–Meier curves and Cox proportional hazards models were employed to analyze the correlation between RAR and all-cause mortality at 30, 90, 180, and 365 days. The dose–response relationship was assessed using restricted cubic splines (RCS), and subgroup sensitivity analyses were conducted to evaluate the robustness of the results.ResultsPatients in the highest RAR group (Q4, 7.18–8.38) exhibited higher baseline inflammation and disease severity. The 30-day and 365-day mortality rates were 31.47 and 36.33%, respectively, significantly higher than those in the Q1 group (6.67 and 8.58%). After multivariate adjustment (age, gender, SOFA/APSIII scores, etc.), the 30-day mortality risk in the Q4 group was 2.13 times greater than that in the Q1 group (HR = 2.13, 95%CI: 1.54–2.99), and the 365-day risk was 2.17 times greater (HR = 2.17, 95%CI: 1.61–2.93). RCS indicated a linear positive correlation between RAR and mortality rates (non-linearity p > 0.05), and sensitivity analyses suggested that the trend of increased mortality risk with higher RAR was consistent across different subgroups of age, gender, mechanical ventilation status, and comorbidities (interaction p > 0.05), indicating the universality of the predictive efficacy.ConclusionRAR serves as an independent predictor of all-cause mortality in critically ill patients with COPD. As a low-cost and readily available biomarker, this index has the potential to provide new insights for risk stratification of ICU patients. However, further prospective studies are needed to confirm its clinical translation value.